2004
DOI: 10.1590/s0100-879x2004000100018
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine profile in the subclinical form of visceral leishmaniasis

Abstract: The factors determining the development or not of visceral leishmaniasis (VL) have not been completely identified, but a Leishmaniaspecific cellular immune response seems to play a fundamental role in the final control of infection. Few studies are available regarding the production of cytokines in the subclinical form of VL, with only the production of IFN-γ and TNF-α known. The aim of the present study was to identify immunological markers for the oligosymptomatic or subclinical form of VL. A prospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 24 publications
0
27
0
5
Order By: Relevance
“…In contrast, other studies found minimal levels of this cytokine in Indian VL patients (74,90,91). Moreover, TNF-␣ was also present in asymptomatic VL patients (83), complicating the interpretation of TNF-␣ in cases of VL. For CL patients, studies of TNF-␣ serum levels are contradictory; some studies found elevated levels of TNF-␣ in the plasma of CL patients that decreased posttreatment compared to healthy controls (92)(93)(94)(95), but others could confirm this only for MCL patients (85,96).…”
Section: Identified Biomarkersmentioning
confidence: 87%
See 2 more Smart Citations
“…In contrast, other studies found minimal levels of this cytokine in Indian VL patients (74,90,91). Moreover, TNF-␣ was also present in asymptomatic VL patients (83), complicating the interpretation of TNF-␣ in cases of VL. For CL patients, studies of TNF-␣ serum levels are contradictory; some studies found elevated levels of TNF-␣ in the plasma of CL patients that decreased posttreatment compared to healthy controls (92)(93)(94)(95), but others could confirm this only for MCL patients (85,96).…”
Section: Identified Biomarkersmentioning
confidence: 87%
“…TNF-␣ levels were found to be significantly increased in patients with active VL (77,(83)(84)(85); they declined during treatment (85-89) and returned to healthy-control levels at the end of treatment (84). Unresponsive patients retained elevated levels of TNF-␣ (85).…”
Section: Identified Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite a highly activated immune system, patients exhibit Leishmania antigenspecifi c immunosuppression 12 . Additionally, interleukin 10 (IL-10) and TGF-β activity in splenic and liver macrophages induces parasite proliferation; therefore, these cytokines can be characterized as immune response regulators [13][14][15][16][17][18] . It has been suggested that the main risk factors for death in VL are related to the fact that such high systemic pro-infl ammatory cytokine production greatly compromises organs and systems 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Treated individuals develop a cell-mediated immune response capable of offering protection from reinfection, as characterized by antigen-specific IFN-␥ responses (7,34). In contrast, individuals with advanced VL show a decrease in antigen-specific IFN-␥ production and elevated levels of the immunoregulatory cytokine IL-10 in serum and increased IL-10 mRNA expression in lesional tissue (6,10). The correlation between VL disease progression and IL-10 production in humans is now well established (22).…”
mentioning
confidence: 99%